1987
DOI: 10.1067/mva.1987.avs0050796
|View full text |Cite
|
Sign up to set email alerts
|

Distal arterial reconstruction: Patency and limb salvage in diabetics

Abstract: Controversy regarding efficacy and durability of distal bypass grafting of the diabetic patient exists. A 22-year-long series of 259 vascular procedures with 100% follow-up (57% in diabetic individuals) is examined to compare these results with those of non-diabetic patients. Extensive review of predisposing factors, operative indications, preoperative medical evaluation, as well as techniques and peculiarities of angiography is rendered. Peripheral arterial case mix between the two groups is examined. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…Moreover, in distal bypass grafting, the diabetic patients may have better cumulative graft patency as compared to non-diabetic patients. 10,11 Similarly, in our study, the patency rates were similar in diabetic and non-diabetic patients, both in the total cohorts of patients as well after the application of the propensity score matching. However, in Japan population, diabetes mellitus has been reported to be a possible determinant factor of graft failure.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, in distal bypass grafting, the diabetic patients may have better cumulative graft patency as compared to non-diabetic patients. 10,11 Similarly, in our study, the patency rates were similar in diabetic and non-diabetic patients, both in the total cohorts of patients as well after the application of the propensity score matching. However, in Japan population, diabetes mellitus has been reported to be a possible determinant factor of graft failure.…”
Section: Discussionsupporting
confidence: 80%
“…These findings of increased incidence of tissue loss for diabetics have also been reported by other authors. 3,15,16 The operative mortality rate was similar for diabetics and nondiabetics and stayed below 2%, which is the same rate for the current largest dorsalis pedis bypass series from Pomposelli and colleagues. 12 However, others have shown a trend toward an increase 9 or a significant 10 increase in operative mortality for pedal reconstruction compared to that for tibial or peroneal reconstructions.…”
Section: Discussionsupporting
confidence: 60%
“…Improved graft patency in diabetics over that in nondiabetics had previously been shown by others but for infrainguinal bypasses at large. 5,15 Other authors have shown the same outcome in diabetics as in nondiabetics with regard to both graft patency and limb salvage rates for popliteal or tibial artery bypasses. 3,4 Rutherford et al 5 attributed improved patency of infrainguinal reconstructions in diabetic patients to greater use of autogenous vein in reconstruction and lower tobacco use by patients.…”
Section: Discussionmentioning
confidence: 93%
“…18 The primarily distal popliteal and tibial pattern of peripheral vascular occlusive disease associated with diabetes has been well described. 19,20 The high risk of severe foot infections in diabetes is similarly acknowledged. 21 Even in patients who are nondiabetic with premature coronary artery disease, insulin and proinsulin levels tend to be elevated, especially in African Americans.…”
Section: Discussionmentioning
confidence: 99%